Evaluation of different methods for determining ammonia emissions in poultry buildings and their applicability to open facilities (2013)
In regions of tropical and subtropical climates, nearly all installations used for intensive broiler chicken production and other animals of economic interest operate as curtain-sided open structures with assisted mechanical ventilation. The lack of ventilation control in these facilities, along with wind direction and velocity effects on ventilation uniformity, complicates calculation of the quantity of gases (ammonia and others) generated by the litter at a given moment. This fact constitutes a pitfall when evaluating the polluting potential of open environments, and when comparisons with data encountered in closed environment facilities used in temperate climates need to be done. All developed countries of Europe and North America already possess methodologies to determine gas emissions in closed installations commonly found in these regions. Therefore, the objective of the present study was to evaluate some specific methodologies used for determining ammonia emissions from broiler houses located in countries of Europe and the United States, and verify the possibility for application of these methodologies to open structures commonly found in Brazil and other countries of South America. A quantitative evaluation showed that the methods with best characteristics for adaptability to the operational conditions and the different types of conditioned environments of buildings with positive pressure or natural ventilation systems were the internal tracer gas, the portable monitoring unit (PMU) and the mobile air emissions monitoring unit (MAEMU). According to the results, model-based approaches that use mass balance and passive diffusion samplers such as the “Ferm Tube” and the Saraz Method for Determination of Ammonia Emissions (SMDAE) proposed by Osorio (2010), can also be adapted to different operational conditions for open buildings.